Perjuangan Tuan Guru Bangkol dalam Suku Sasak: Analisis Representasi Tokoh dalam Naskah Babad Praya Koleksi Museum NTB - Mamlahatun Buduroh; Anisa, Mozeea Kiara (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2025)
Babad Praya is a classic Lombok manuscript that tells the struggle of the Sasak Praya tribe to escape the rule of Karangasem Bali. An important character in this story is Tuan Guru Bangkol. This study discusses Tuan Guru Bangkol as a representation of Sasak tribal warrior figures in Babad Praya. This study aims to describe the role of Tuan Guru in the social life of the Sasak people and focuses on the resistance of Tuan Guru Bangkol as the warlord of Praya II in 1891-1894. The main source of data for this research is the transliteration of the Babad Praya manuscript by Lalu Gde Suparman. Furthermore, in reviewing the text, descriptive qualitative research methods are used with the representation theory approach of Jacob Sumardjo and Stuart Hall. The results of this study show that Tuan Guru Bangkol played an important role in liberating the Sasak community of Lombok from the rule of Karangasem. Tuan Guru Bangkol is a representative of fighters who have a major role in the resistance of the Sasak people against Karangasem. He acted as a warlord as well as the leader of the Qadiriyah wa Naqsabandiyah tarikat.